Site and Stage of Colorectal Cancer Influence the Likelihood and Distribution of Disease Recurrence and Postrecurrence Survival: Data From the FACS Randomized Controlled Trial. Issue 6 (June 2016) - Pugh, Siân A.; Shinkins, Bethany; Fuller, Alice; Mellor, Jane; Mant, David; Primrose, John N.
Abstract : Objectives: To describe patterns of recurrence and postrecurrence survival in a large cohort of accurately staged patients with Dukes' A-C colorectal cancer. Background: Recurrence remains a frequent cause of mortality after the treatment of colorectal cancer with curative intent. Understanding the likelihood and site of recurrence informs adjuvant treatment and follow-up. Methods: Retrospective cohort analysis of data from the FACS (follow-up after colorectal cancer surgery) trial after a median 4.4 years of follow-up; postrecurrence survival was calculated using the Kaplan-Meier method. Results: Complete data were available for 94% of patients; 189 (17%) patients had experienced recurrence. Incidence of recurrence varied according to the site of the primary (right colon: 51/379, 14%; left colon: 68/421, 16%; rectum: 70/332, 21%; P = 0.023) and initial stage (Dukes' A: 26/249, 10%; Dukes' B: 81/537, 15%; Dukes' C: 82/346, 24%; P < 0.0001). Pulmonary recurrence was most frequently associated with rectal tumors, and multisite/other recurrence with right-sided colonic tumors. Recurrences from lower-stage tumors were more likely to be treatable with curative intent (Dukes' A: 13/26, 50%; Dukes' B: 32/81, 40%; Dukes' C: 20/82, 24%; P = 0.03). Those with rectal tumors benefited most from follow-up (proportion with treatable recurrence: rectum 30/332, 9%; left colon 23/421, 6%; right colon 12/379, 3%; P = 0.003). Both initial stage (log rank P = 0.005) and site of primary (log rank P = 0.01) influenced postrecurrence survival. Conclusions: The likelihood and site of recurrence, and survival, are influenced by the site and stage of the primary tumor. Those with rectal cancers benefited most from follow-up. ISRCTN 41458548